Stabilised oxygen nutritional supplement on cycling performance - Singh, Rabindarjeet; Larmie, E.T. (2001)
The basic physiologic response to exercise is an increase in total body oxygen consumption made possible by increase in pulmonary ventilation,cardiac output and oxygen extraction by the tissues.A given work load requires a specific amount of energy.This energy is mainly from aerobic metabolism. Although the energy released in glycolysis is rapid and does not require oxygen,relatively little ATP is resynthesised.It is the aerobic metabolism reaction that takes place in the mitochondria that provides the all important energy sources.Therefore,exercise that is carried out at low to moderate intensity rely solely on aerobic metabolism. As exercise prolongs or becomes heavy, the oxygen supply becomes inadequate or the energy demands outstrip cellular capacity for aerobic resynthesis of ATP. Under conditions of oxygen deficiency, the energy requirement is met by the predominance of anaerobic glycolysis.